ELLIPSIS IN ROBERT LOUIS STEVENSON’S TREASURE ISLAND NOVEL - Rusman Roni; Magdad Hatim; Oktri Syaifura (ELTE Journal (English Languange Teaching and Education), 2017)
This article was aimed to find out what ellipses were used and how ellipses were expressed in Robert Louis Stevenson’s Treasure Island novel. This article also used qualitative approach and content analysis technique. In addition, Documentation was the technique to collect the data taken from Robert Louis Stevenson’s Treasure Island novel. The data were taken from all sentences and utterances in that novel. From the data analyzed, it was found that there were three types of ellipsis elements occurred in analysis of ellipsis in Robert Louis Stevenson’s Treasure Island; they were nominal, verbal and clausal ellipsis. Those types of ellipsis were expressed in narrative sentences and utterances. The most frequent types were clausal ellipsis occurred 168 times (47.73%). This type also omitted clausal elements or subject pronoun. Nominal ellipsis occurred 108 times (30.68%). This type occurred when a noun or noun phrase is omitted or presupposed. Verbal ellipsis was the fewest types used in Robert Louis Stevenson’s Treasure Island novel which occurred 76 times (21.59%). This type occurred when a verb or verb phrase is omitted and it had two common types, echoing and auxiliary contrasting. Moreover, this study would give contribution for teachers, students, English learners and other researchers related to the use of three types of ellipsis.Keywords: Analysis, nominal ellipsis, verbal ellipsis and clausal ellipsis.